INSIGHTS INTO ELT CURRICULUM IMPLEMENTATION IN INDONESIA: CHALLENGES, TRENDS, AND IMPLICATIONS - Sulistiyani, Sulistiyani; Prihantini, Apsari Fajar; Kristanto, Wisnu; Jannah, Fitri yatul; Efendi, Tri Achmad (Jurnal IKA PGSD (Ikatan Alumni PGSD) UNARS, 2025)
The implementation of the English Language Teaching (ELT) curriculum in Indonesia continues to face challenges despite numerous reforms, including the transition from the 2013 Curriculum to the Merdeka Curriculum. This systematic literature review examines 37 studies published between 2013 and 2024 to identify trends and challenges in ELT curriculum implementation. Findings reveal that qualitative research methodologies, especially case studies and descriptive approaches, dominate the field. The primary challenges identified include limited teacher competence and proficiency, pedagogical and practical issues, and student-related challenges. Teachers often lack sufficient English proficiency and pedagogical skills to implement innovative approaches like Communicative Language Teaching (CLT), the Scientific Approach, and Genre-Based Approaches (GBA). Additionally, low student motivation and passive learning behaviours persist, further hindering curriculum effectiveness. The study suggests enhancing professional development to equip teachers with practical skills and curriculum familiarity. Practical and contextualized curriculum guidelines and comprehensive evaluation mechanisms are also needed to bridge the gap between policy and classroom practice. Addressing these challenges is essential for improving ELT outcomes in Indonesia.